Analysis of the shear failure of surface methane capture boreholes for improving the drainage period efficiency: A lithological perspective. Issue 1 (January 2020) - Xu, Hongjie; Fang, Zezhong; Sang, Shuxun; Liu, Huihu; Ding, Hai; Dou, Xinzhao; Liu, Qinjie
The shear failure of surface methane capture boreholes (SMCBs) is the main reason for the life cycle shortening of surface methane capture boreholes but lacks a comprehensive lithological analysis. To improve the surface methane capture borehole stability and drainage period efficiency, it is of great importance to investigate the influence of lithology on the shear failure of surface methane capture boreholes. The results of direct shear tests and geological investigations show that the shear displacement increases as the grain size decreases. A jump in mechanical properties occurs at the lithological boundaries and is mainly controlled by the composition of the rock specimens. The change in cohesion is the main possible reason for the step change of the shear strength. High quartz and low clay contents may effectively improve the shear strength and failure resistance of rock. Boreholes may potentially experience preferential casing failure in the section of the weaker mudstone and siltstone due to larger shear displacements and lower shear strengths of those rock types. Protective measures at these sections may improve the stability of the borehole casing. The detection results at the close of the borehole verify the prediction.